1980
DOI: 10.1002/1520-6807(198004)17:2<257::aid-pits2310170218>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of imaginative play actions on language development in five-year-old children

Abstract: The study, using 60 five-year-olds, investigated forms of play: (a) self-action, (b) puppet-action, and (c) control treatments and differences between the sexes on aural language recall scores using semantic, absolute, and syntactic criteria. The results of the preliminary analyses between treatment groups and sex differences on the Peabody Picture Vocabulary Test and the Harris-Goodenough Draw-A-Man Test indicated no significant main or interaction effects. The subjects in treatment groups and boys and girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…Thus, there was confirmation of Hypothesis 1, which proposed that the programme would stimulate an increase in verbal intelligence, and of Hypothesis 3, which proposed an increase in the capacity for verbal associative thinking. Moreover, these results are in the same line as those of other studies, which have confirmed a positive effect of play in the development of verbal intelligence-of language (Dansky, 1980a(Dansky, , 1980bFisher, 1992;Garaigordobil, 1992Garaigordobil, , 1995aGaraigordobil, , 1996aGaraigordobil, , 2003aLevy et al, 1992;Marbach & Yawkey, 1980;McCune-Nicolich, 1981;Price-Coffee, 1995;Saltz et al, 1977;Udwin, 1983;Vedeler, 1997;Yawkey, 1986). Thus, the present study supports the positive effect of interventions that stimulate cooperative and creative play-that promote prosocial behaviour-on intellectual factors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, there was confirmation of Hypothesis 1, which proposed that the programme would stimulate an increase in verbal intelligence, and of Hypothesis 3, which proposed an increase in the capacity for verbal associative thinking. Moreover, these results are in the same line as those of other studies, which have confirmed a positive effect of play in the development of verbal intelligence-of language (Dansky, 1980a(Dansky, , 1980bFisher, 1992;Garaigordobil, 1992Garaigordobil, , 1995aGaraigordobil, , 1996aGaraigordobil, , 2003aLevy et al, 1992;Marbach & Yawkey, 1980;McCune-Nicolich, 1981;Price-Coffee, 1995;Saltz et al, 1977;Udwin, 1983;Vedeler, 1997;Yawkey, 1986). Thus, the present study supports the positive effect of interventions that stimulate cooperative and creative play-that promote prosocial behaviour-on intellectual factors.…”
Section: Discussionsupporting
confidence: 92%
“…A difference between this work and other studies that have shown the effectiveness of play in the development of language (Dansky, 1980a;Dockett, 1998;Levy et al, 1992;Marbach & Yawkey, 1980;McCune-Nicolich, 1981;Price-Coffee, 1995;Saltz et al, 1977;Udwin, 1983) lies in its showing that play not only has this effect during the preschool stage, but also throughout childhood. Moreover, the majority of studies have demonstrated these effects through the study of sociodramatic play, and in this work not only sociodramatic play, but also cooperative games in general, with or without representative activity, promote the development of verbal intelligence.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This active experience could have benefited children's detection of the possibility for analogy and their extrapolation of the solution to the target problem. Having previously enacted the solution would make it cognitively available to them when confronted with the analogous problem; both children and adults show better memory when they have enacted something with their bodies (Marbach & Yawkey, 1980;Scott, Harris, & Rothe, 2001). Future work could vary whether children have the opportunity to enact a solution or only observe it during a play period to test this prediction.…”
Section: Learning From Pretense Vs Realitymentioning
confidence: 99%